Some properties of a generalized multiplier transform on analytic p-valent functions - Hamzat, J. O.; El-Ashwah, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5 For a function f(z)=z^p+^∞_k=1 a_k+pz^k+p, where pN, the authors investigate some properties of a more general multiplier transform on analytic p-valent functions in an open unit disk. The applications of the obtained results to fractional calculus are pointed out, while several other corollaries follow as simple consequences.